The influence of occupational values on college students’ willingness to apply for civil servants: The mediating role of political efficacy - Ni, Jianchao; Shen, Yuanyi; Chen, Chunmei; Liu, Xiangfu (Frontiers in Psychology, 2022)
In the post-epidemic era, college students are facing new challenges for job hunting and employment. At present, civil servant positions have become the main employment target of many college students in China, and there is a deep motivation behind this phenomenon. Based on the theories of occupational values, public service motivation, and political efficacy, this research conducted an empirical study on 580 college students by using occupational values scale, political efficacy scale and the willingness to apply for civil servants scale. Through regression analysis and structural equation model analysis, this research explored the influence of occupational values on college students' willingness to apply for civil servants and analyzed the mediating role of political efficacy. The results show that: (1) The dimensions of career stability, prestige value and public service motivation of occupational values have significant positive impacts on college students' willingness to apply for civil servants, among which public service motivation has the most significant impact. (2) Occupational values have significant positive impacts on college students' political efficacy. (3) Political efficacy has a significant positive impact on the willingness of college students to apply for civil servants. (4) Political efficacy plays a partial mediating role in the transmission path of occupational values and willingness to apply for civil servants.